2019
DOI: 10.12968/ijpn.2019.25.6.274
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of nurses towards euthanasia: a cross-sectional study in Iran

Abstract: Background: Nurses play a major role in providing end-of-life care, and euthanasia is considered to be one of the most important ethical challenges that care providers can face. Aim: To assess the nurses' attitude towards euthanasia in Iran. Methods: The cross-sectional study included nurses who worked in intensive and critical care, as well as dialysis units of a teaching hospital affiliated to Zahedan University of Medical Sciences, who were selected by the census sampling technique. Data were collected usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 28 publications
4
10
3
Order By: Relevance
“…2,5 There are a lot of ambiguous subject matter about doing euthanasia by nurses in the world inclusive of whether euthanasia conflicts with their autonomy, competence, and dignity of nurses. 9 In this regard in Belgium, euthanasia should be conducted in consultation with nurses, which indicates the importance of knowing nurses' attitudes toward euthanasia. 5 In Canada, registered nurses and nurse practitioner can perform euthanasia; therefore the clinical role of nurses is much greater than what is stated in the law.…”
Section: Introductionmentioning
confidence: 99%
“…2,5 There are a lot of ambiguous subject matter about doing euthanasia by nurses in the world inclusive of whether euthanasia conflicts with their autonomy, competence, and dignity of nurses. 9 In this regard in Belgium, euthanasia should be conducted in consultation with nurses, which indicates the importance of knowing nurses' attitudes toward euthanasia. 5 In Canada, registered nurses and nurse practitioner can perform euthanasia; therefore the clinical role of nurses is much greater than what is stated in the law.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses clearly play an important role in providing the necessary end-of-life care 24 h a day, not only in symptom control and pain management so important in certain terminal illnesses, but also in the emotional support they provide to the dying patient and their family [24]. It is therefore not surprising that they are the first to receive the first demand for euthanasia and therefore to be aware of the importance of getting involved in the current debate about euthanasia [25].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these limitations, a secondary search strategy was performed as follows. The references listed in the 46 selected articles 1,3,5,6,[8][9][10][11][12][13][15][16][17][20][21][22][23][24][25][26]29,30,32,33,36,[40][41][42][43][44]46,[48][49][50][51][52][53][54][55][56][57]59,66,[71][72][73] were checked for further relevant references, and religious books (Quran and hadith) and legal codes of selected countries were also consulted from websites. The secondary search strategy resulted in an additional 30 references, which we included in this review.…”
Section: Methods For Literature Searchmentioning
confidence: 99%
“…Few studies have been conducted in Iran reviewing nurses' and nursing students' attitudes to euthanasia. [49][50][51][52] In one study, the majority of Muslim nurses (60%) were found to have negative attitudes towards euthanasia. 50 Another study found that around 34% of nursing students had a negative attitude towards euthanasia, while 42% and 24% reported a neutral and positive attitude, respectively.…”
Section: Attitudes Of Muslims Towards Physicianassisted Suicide and Ementioning
confidence: 99%
See 1 more Smart Citation